Natural Resistance in Shisham Clones against a Defoliator Plecoptera reflexa Guen. (Lepidoptera : Noctuidae) in Foothills of Himachal Pradesh - Singh, Charan; Pandey, V. P. (Indian Forester, 2007)
No abstract